Heterogeneity in Preferences for Primary Care Consultations: Results from a Discrete Choice Experiment - Mengoni, Alessandro; Seghieri, Chiara; Nuti, Sabina (International Journal of Statistics in Medical Research, 2013)
Purpose: The increasing importance of flexibility in the general practitioner (GP) -patient consultation approach in primary care requires healthcare managers and physicians to find a balance among all the potentially important characteristics of consultation. This study used a discrete choice experiment (DCE) to assess patients’ preferences for different attributes of GP consultation and how the rate at which they traded between different attributes is affected by socio-demographic characteristics and past experiences with primary care services . Methods: A survey was conducted to a sample of 6970 residents in Tuscany region, Italy. Besides socio-demographic characteristics the survey collected information about participants’ past experience with GP consultation in the last 12 months. Moreover, participants were asked to select their preferred option in a series of pairwise choices, defined by the following attributes: level of involvement in decision making, amount of information received from the GP and waiting time for the visit. Results: Results revealed that receiving information from the GP was more important than being involved in the decisions and that, approximately, a complete involvement had the same importance as a partial involvement. Participants' past experience with GP’s consultation appeared to have the greatest influence on the involvement level. The amount of information required by the respondents was also influenced by a complex interplay of personal and contextual factors. Conclusions: This large-scale study extends the body of literature on DCE applications for different GP consultation approaches, providing new information about the influence that patients’ socio-demographic characteristics and past experiences could have on consultation preferences.